Bioactive coating on titanium implants modified by Nd:YVO4 laser - de Almeida Filho, Edson [UNESP] (2011)
Apatite coating was applied on titanium surfaces modified by Nd:YVO4 laser ablations with different energy densities (fluency) at ambient pressure and atmosphere. The apatites were deposited by biomimetic method using a simulated body fluid solution that simulates the salt concentration of bodily fluids. The titanium surfaces submitted to the fast melting and solidification processes (ablation) were immersed in the simulated body fluid solution for four days. The samples were divided into two groups, one underwent heat treatment at 600 degrees C and the other dried at 37 degrees C. For the samples treated thermally the diffractograms showed the formation of a phase mixture, with the presence of the hydroxyapatite, tricalcium phosphate, calcium deficient hydroxyapatite, carbonated hydroxyapatite and octacalcium phosphate phases. For the samples dried only the formation of the octacalcium phosphate and hydroxyapatite phases was verified. The infrared spectra show bands relative to chemical bonds confirmed by the diffraction analyses. The coating of both the samples with and without heat treatment present dense morphology and made up of a clustering of spherical particles ranging from 5 to 20 mu m. Based on the results we infer that the modification of implant surfaces employing laser ablations leads to the formation of oxides that help the formation of hydroxyapatite without the need of a heat treatment. (C) 2010 Elsevier B.V. All rights reserved.